A Critical Introspection of Abortion Laws in Nigeria - Ifeoluwayimika Bamidele; Precious Fasuyi (ABUAD Journal of the Humanities-AGIDIGBO)
An abortion is a procedure to end pregnancy, either by surgery or Medicine. The procedure is expected to be done by a licensed health care professional. Abortion is however illegal in Nigeria as there are legislations which prohibit abortion except in cases where the carriage of the pregnancy to term is detrimental to the health and life of the mother. Statistics has shown that 1,000 out of 100,000 maternal deaths stem from the estimated 1,000,000 abortions done in the country annually. Unfortunately, the law on abortion in Nigeria fails to recognize the actual state of happenings, this has in a way given room for illegal abortion and high maternal mortality rate in Nigeria. The main focus of this paper is to explore abortion practices and it’s regulation in Nigeria, how the laws on abortion in Nigeria affects healthcare and maternal mortality rates and whether or not the present abortion laws are still relevant to the milieu of the average Nigerian woman. This paper relies on existing literature for data and this literature suggests that the present abortion laws are heavily influenced by religion and faux morality rather than empirical evidence to the effects of abortions in the society. This paper investigates both influences and recommends a different approach to abortion legislation and calls for a reformation of the laws on abortion in Nigeria. It concludes that abortions should be made legal in the first trimester of pregnancy  when it is safe for the mother.